Aesthetic Evaluation After Three-Dimensional Shaping of Free Flap for Nasal Reconstruction without Additional Paramedian Forehead Flap - Atmodiwirjo, Parintosa; Jonathan, Reinhart; Ramadan, Mohamad Rachadian; Triatmoko, Sara Ester; Erina, Maryam Nur; Ralena, Nadhira Anindita (Jurnal Plastik Rekonstruksi, 2022)
Nasal reconstruction has continued to advance in accordance with Menick's vision as it was first conceived. His combination of radial forearm free flaps with the gold standard of paramedian forehead flaps is highly regarded for producing superior outcomes, and it has received widespread praise as a consequence. In this study, we present nine patients who had nose reconstruction using free flaps. All of the patients had successful outcomes. Using the FACE-Q questionnaire, we assessed the degree to which patients were satisfied with both the functional and aesthetic aspects of their appearance. The outcomes were positive for nine of the patients.